Iron oxide nanoparticles stable in the human body? - Requejo-Roque, Katherinne Isabel (2011)
Currently, it is possible to obtain iron oxide nanoparticles soluble in water with high stability in biological environments through thermal decomposition at high temperatures and ligand exchange. This method of synthesis allows good control of size distribution in order to obtain monodispersed nanoparticles with surfaces suitable for functionalization which is necessary for biological applications.